Optimization of window-to-wall ratio with sunshades in China low latitude region considering daylighting and energy saving requirements. (1st January 2019) - Xue, Peng; Li, Qian; Xie, Jingchao; Zhao, Mengjing; Liu, Jiaping
Graphical abstract: Highlights: Optimization process of WWR for buildings in China low latitude area is proposed. Sunshade configurations are integrated in evaluating building performances. Optimal WWR ranges are found based on daylighting and energy-saving principles. Largest WWR could reach to 0.78 with comprehensive sunshade for south-facing units. Proposed design scenarios are verified and optimization process could be promoted. Abstract: Daylight is a valuable resource with characters of both photometry and radiometry, and window-to-wall ratio (WWR) is a crucial building envelope element that decides the indoor luminous and thermal environments. Due to the traditional utilize of external shadings and lack of appropriate design standard for buildings in China low latitude region, this study proposes a workflow for optimizing WWR with sunshades by considering both daylighting performance and energy consumption. The reference WWR is firstly decided based on the requirements of daylighting standards by using Radiance for standard room without external shading, and the reference annual cooling load of the whole building is then calculated by EnergyPlus. A large number of cases with different WWRs and external shadings are calculated and energy-saving and daylighting performances are finally verified with reference case. The optimal WWR value range with different sunshades configurations in different orientations is that meets daylighting requirement while below reference annual cooling load. The results indicate that comprehensive sunshades have the best energy performance with the benefits of both horizontal and vertical ones. With a 1.8 m comprehensive sunshade, the lower threshold of WWR raises to 0.40 for meeting daylighting requirement, and the accepted upper threshold of WWR range for west, north, east and south-facing units could reach to 0.56, 0.6, 0.6 and 0.78 respectively. For designing a building with façade the same in all orientations, the largest WWR could be set as 0.7 for west-east buildings and 0.55 for south-north buildings with 1.8 m comprehensive sunshades. The scenario has been verified and this WWR optimization process could be applied to different buildings in other climate regions.